Моделювання процесів сталого розвитку полімерної тари та пакування на стадіях її експлуатаціі і утилізації - Ольховська, Вікторія Олегівна; Бухкало, Світлана Іванівна (Яроче́нко Я. В., 2022)
In accordance with the analysis of the development of modern areas of solving problems related to sustainable development of technological, environmental and social systems, priority issues of solid waste disposal and its specific components according to our research in the field of polymer waste disposal shows the feasibility of complex polymer waste disposal companies.
Keywords: полімери; тара; пакування; утилізація; відходи